Field Study of Gregarious Flowering and Use of ENM in Conservation Strategies for Gigantochloa andamanica (Kurz) Kurz in Andaman Islands (India) - Kumari, Pushpa; Lakra, Reshma (Plantae Scientia, 2019)
Gregarious flowering in bamboo species is a periodic event which affects the habitat’s ecology, since the whole population die within same time frame. The phenomenon sets effects on the social economy too as bamboo is one of the most important natural resources people depends on. In this paper gregarious flowering and mass seeding in Gigantochloa andamanica (Kurz) Kurz, an economically important bamboo species of Andaman Islands have been reported with effective conservation strategies to balance the population in natural habitat. This also includes the description, illustration, photo plates of the species for the easy identification, the ENM map based on the GPS data collected for the distribution area and data relevant to traditional and economic uses of the species. This study more importantly shows the application of ENM for the identification of suitable sites for field reintroduction of the seedlings in natural habitats aimed at their better growth and survival.